Molecular mechanisms of OXR1 function - Liu, K (2014)
By 2040, the World Health Organization expects neurodegenerative diseases, such as Alzheimer’s disease, amyotrophic lateral sclerosis (ALS), and Parkinson’s disease, to surpass cancer as the second most common cause of death worldwide. Currently, only treatments for symptoms of these diseases are available. Thus, research is critical to alleviate this public health burden by elucidating the pathogenic processes and developing novel therapies. While exact mechanisms by which these heterogeneous neuropathological conditions become manifest in patients remain unclear, growing evidence suggests that oxidative stress (OS) makes a significant contribution to neuronal dysfunction and apoptosis in all major neurodegenerative diseases. Recently, the gene oxidation resistance 1 (Oxr1) has emerged as a critical regulator of neuronal survival in response to OS. Oxr1 is expressed throughout the central nervous system, and its highly conserved TLDc domain protects neurons from oxidative damage through an unknown mechanism. This thesis aimed to define mechanisms by which Oxr1 confers neuronal sensitivity to OS, and to determine its role in neurodegenerative diseases. I found that Oxr1 mediates cytoplasmic localization of ALS-associated proteins Fused in Sarcoma (FUS) and transactive response DNA binding protein 43 kDa (TDP-43) through a TLDc domain- and arginine methylation-dependent pathway. Next, I investigated in vivo neuroprotective functions of Oxr1, and demonstrated that neuronal Oxr1 over-expression extends survival and ameliorates behavioural dysfunction and pathology of an ALS mouse model. In particular, neuronal Oxr1 over-expression strikingly delays neuroinflammation during ALS pathogenesis. Finally, I characterised a mouse model that specifically deletes Oxr1 from motor neurons. While loss of Oxr1 in ChAT-positive motor neurons does not cause overt neurodegeneration in the spinal cord, constitutive loss of Oxr1 leads to neuroinflammation in the cerebellum and spinal cord. Taken together, these studies illuminate functions of Oxr1 in the complex antioxidant defence network and present implications for future therapeutic strategies.